Efektivitas Program Posyandu dalam Meningkatkan Status Gizi Balita di Daerah Terpencil - Hasbi, Saipul; Huraiman, Sulaeman (Journal of Medical and Health Sciences, 2025)
The Posyandu program is one of the government's strategic efforts to improve public health, especially toddlers, through community-based basic health services. This study aims to analyze the effectiveness of the Posyandu program in improving the nutritional status of toddlers in remote areas. The research method used is a quantitative approach with a cross-sectional study design. Data were collected through a survey of 120 mothers of toddlers who actively participated in Posyandu activities in three remote villages. Nutritional status parameters were measured based on anthropometric indicators (weight for age, height for age, and weight for height) before and after the program intervention for six months. The results showed a significant increase in the nutritional status of toddlers after participating in the Posyandu program routinely, with a decrease in the prevalence of undernourished toddlers from 27% to 15%. Factors that contributed to the success of the program included the active involvement of cadres, the availability of additional food, and targeted nutritional counseling. This study concluded that the Posyandu program was effective in improving the nutritional status of toddlers in remote areas, although strengthening in terms of facilities, cadre training, and program continuity was still needed.